DEC205 mediates local and systemic immune responses to Helicobacter pylori infection in humans - Kita, Masahide (Oncotarget, 2018)
Helicobacter pylori infections cause gastritis and affect systemic immune responses; however, no direct association between immune cells and stomach bacteria has yet been reported. The present study investigated DEC205-mediated phagocytosis of H. pylori and the role of DEC205-positive macrophages in the human gastric mucosa. DEC205 mediated phagocytosis of H. pylori was detected immunocytochemically in PMA-stimulated macrophages differentiated from NOMO1 cells. Expression of DEC205 mRNA in peripheral blood mononuclear cells (PBMCs) from H. pylori-infected patients was analyzed following stimulation with H. pylori cell lysate. We found that anti-DEC205 antibodies inhibited phagocytosis of H. pylori. The number of cells double-positive for DEC205 and CD14 in human gastric mucosa was higher in H. pylori-infected patients. DEC205-positive macrophages invaded the extracellular space between epithelial cells within gastric pits. In addition, DEC205 mRNA expression was upregulated in human PBMCs stimulated with H. pylori lysate. These findings suggest DEC205-expressing macrophages are important for recognition of H. pylori in human gastric mucosa, which affects systemic immunity.